A COMPARATIVE STUDY OF TWO EFL WHILE-LISTENING TECHNIQUES - BALABAN, Sezen; CAMLİBEL-ACAR, Zeynep (The Eurasia Proceedings of Educational and Social Sciences, 2016)
In foreign or second language learning contexts, listening is often considered an essential yet undermined skill (Bidabadi, 2011; Scarcella & Oxford, 1992). In order to emphasize and increase the effectiveness of this ‘least-wondered skill’, innovative tools need to be researched. To this end, this study has aimed at investigating the use of two distinct while-listening techniques in EFL (English as a foreign language) lessons, namely ‘shadowing’ and ‘note-taking’. The major focus was to analyse the impact of these techniques on learners’ listening comprehension ability and changes in their perceptions of listening lessons and their own listening abilities. Specifically, the following research questions were asked: 1) which of the two while-listening techniques, namely ‘shadowing’ or ‘note-taking’, improves learners’ listening comprehension to a higher extent? and 2) how does each while-listening technique influence learners’ perceptions of and attitudes towards listening in the foreign language? The research was conducted with four groups of pre-intermediate level English language preparatory class students at a state university in Turkey. Groups were randomly assigned to receive training on either ‘shadowing’ or ‘note-taking’ from the same instructor for six consecutive weeks. Quantitative data include the pre-and post-test results for listening, as well as scores of comprehension check questions asked at the end of each training session. In addition, learner reflections provide information on students’ opinions and perspectives related with each technique. Quantitative findings indicate a significant difference between groups in terms of learners’ listening scores, and qualitative findings reveal various themes in relation to the techniques.